2001
DOI: 10.1212/wnl.57.4.639
|View full text |Cite
|
Sign up to set email alerts
|

Evidence-based measurement

Abstract: In the sample studied, the BI, FIM, FIM+FAM have similar measurement properties, when examined using traditional psychometric analyses. Although instruments with more items and item response categories generate more qualitative information about an outcome, they may not improve its measurement. Results highlight the importance of using recognized techniques of scale construction to develop health outcome measures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
126
0
5

Year Published

2004
2004
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 212 publications
(143 citation statements)
references
References 23 publications
12
126
0
5
Order By: Relevance
“…Hobart et al compared psychometric properties of the Barthel index with newer and lengthier scales, the Functional Independence Measure (FIM) and the Functional Independence Measure + Functional Assessment Measure (FIM+FAM), in patients undergoing rehabilitation. This study suggested that the newer and more extensive rating scales of FIM and FIM+FAM offered few advantages over the more practical and economical Barthel index [32]. Similar results were observed in studies of patients with multiple sclerosis and stroke [33,34].…”
Section: Discussionsupporting
confidence: 80%
“…Hobart et al compared psychometric properties of the Barthel index with newer and lengthier scales, the Functional Independence Measure (FIM) and the Functional Independence Measure + Functional Assessment Measure (FIM+FAM), in patients undergoing rehabilitation. This study suggested that the newer and more extensive rating scales of FIM and FIM+FAM offered few advantages over the more practical and economical Barthel index [32]. Similar results were observed in studies of patients with multiple sclerosis and stroke [33,34].…”
Section: Discussionsupporting
confidence: 80%
“…The results of the second test were taken as the starting estimate of cognitive function. Decline in basic activities of daily living (ADLs) was assessed using the 20-point variation 38 of the Barthel Index 39 and in extended activities instrumental activities of daily living (IADLs) using a 14-point score. 40 All tests were repeated at 9, 18, and 30 months and at the final trial visit.…”
Section: Measurementsmentioning
confidence: 99%
“…As a result, normative data must be used with caution when making comparisons for this case; however, this further highlights the need for assessing FIM scores by diagnostic category to aid with treatment and discharge planning [36]. The FIM motor subscale scores and the 10-item Barthel Index has reported to be highly correlated [37]. It is believed that the improvements in FIM scores are a result of improvements in motor function.…”
Section: Discussionmentioning
confidence: 95%